2001
DOI: 10.1037/0893-3200.15.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Coparenting: A link between marital conflict and parenting in two-parent families.

Abstract: Coparenting is examined as an explanatory link between marital conflict and parent-child relations in 2-parent families. Data were collected from 3 samples (pilot sample, n = 220 mothers; preadolescent sample, n = 75 couples; preschool sample, n = 172 couples) by using the Coparenting Questionnaire (G. Margolin, 1992b) to assess parents' perceptions of one another on 3 dimensions--cooperation, triangulation, and conflict. Main effects for child's age and for parents' gender were found for cooperation, and an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

37
547
2
98

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 478 publications
(684 citation statements)
references
References 50 publications
37
547
2
98
Order By: Relevance
“…Very few studies have traced links between adult personality traits and coparenting at all, and those that have (Talbot&McHale, 2004;Van Egeren, 2003) have asked how individual personality traits might influence coparenting. But aside from studies examining how coparenting solidarity affects parenting behavior (e.g., Floyd et al, 1998;Margolin, Gordis, & John, 2001), investigators have not asked the reverse question-how having and raising children together might induce personality change and adult development.…”
Section: Coparenting Relationships and Adult Developmentmentioning
confidence: 99%
“…Very few studies have traced links between adult personality traits and coparenting at all, and those that have (Talbot&McHale, 2004;Van Egeren, 2003) have asked how individual personality traits might influence coparenting. But aside from studies examining how coparenting solidarity affects parenting behavior (e.g., Floyd et al, 1998;Margolin, Gordis, & John, 2001), investigators have not asked the reverse question-how having and raising children together might induce personality change and adult development.…”
Section: Coparenting Relationships and Adult Developmentmentioning
confidence: 99%
“…Indeed, increasing evidence highlights that family environment and the quality of parents' relationship with each other following separation may be more important predictors of childhood adjustment than parental separation per se (4). In particular, having parents who can communicate and cooperate in jointly attending to a child's care following separation may protect against adverse psychosocial outcomes in the years following the separation (25)(26)(27)(28). Furthermore, compared with individuals who report poorer childhood family environments, individuals who report more family cohesion and less parental conflict following childhood parental separation endorse fewer health complaints and show decreased risk of morbidity and mortality during adulthood (29,30).…”
mentioning
confidence: 99%
“…Such a finding supported earlier works of Bean et al (2006), Milevsky et al (2006) and Silva et al (2007) where parenting was measured separately for each parent. However, studies conducted by Margolin et al (2001) and McHale et al (2002) demonstrated the need to conceptualise parenting as interdependent concept where relationship between mothers' and fathers' parenting practices were presented as an important contribution to children's functioning, perhaps more important than the individual contributions of mothers' or fathers' parenting styles. Hence, it is necessary to understand that both parents are equally important and have a role to play in supporting their children autonomy and self-reliance.…”
Section: Discussionmentioning
confidence: 99%